Phenotypic spectrum and diagnostic pitfalls of ABCB4 deficiency depending on age of onset - Schatz, Stephanie Barbara; Jüngst, Christoph; Wenning, Daniel (Hepatology communications, 2018)
Genetic variants in the adenosine triphosphate‐binding cassette subfamily B member 4 (ABCB4) gene, which encodes hepatocanalicular phosphatidylcholine floppase, can lead to different phenotypes, such as progressive familial intrahepatic cholestasis (PFIC) type 3, low phospholipid‐associated cholelithiasis, and intrahepatic cholestasis of pregnancy. The aim of this multicenter project was to collect information on onset and progression of this entity in different age groups and to assess the relevance of this disease for the differential diagnosis of chronic liver disease. Clinical and laboratory data of 38 patients (17 males, 21 females, from 29 families) with homozygous or (compound) heterozygous ABCB4 mutations were retrospectively collected. For further analysis, patients were grouped according to the age at clinical diagnosis of ABCB4‐associated liver disease into younger age (<18 years) or adult age (≥18 years). All 26 patients diagnosed in childhood presented with pruritus (median age 1 year). Hepatomegaly and splenomegaly were present in 85% and 96% of these patients, respectively, followed by jaundice (62%) and portal hypertension (69%). Initial symptoms preceded diagnosis by 1 year, and 13 patients received a liver transplant (median age 6.9 years). Of note, 9 patients were misdiagnosed as biliary atresia, Alagille syndrome, or PFIC type 1. In the 12 patients with diagnosis in adulthood, the clinical phenotype was generally less severe, including intrahepatic cholestasis of pregnancy, low phospholipid‐associated cholelithiasis, or (non)cirrhotic PFIC3. Conclusion: ABCB4 deficiency with onset in younger patients caused a more severe PFIC type 3 phenotype with the need for liver transplantation in half the children. Patients with milder phenotypes are often not diagnosed before adulthood. One third of the children with PFIC type 3 were initially misdiagnosed, indicating the need for better diagnostic tools and medical education. (Hepatology Communications 2018;2:504‐514)
Gesehen am 29.05.2019